POSITIONING ELEMENT - WIECEK, Leszek (2025)
The subject of the invention is a positioning element having a convex lower part for mounting on the outlet pipe of the ventilation duct, and a levelling device. It is characteristic for the solution of the invention that it has at least one levelling device (7) provided on the wall of a cylindrical upper part (1). This solution is provided with ribs of the convex lower part that are arranged on the outer surfaces of the convex lower part, and from the upper edge of the convex lower part, the positioning element turns into the cylindrical upper part on which ribs of the cylindrical upper part are arranged. On the outer surface of the positioning element, there are safety-securing elements provided which are seated in a support element.